(untitled) (Fiep Bulletin - online, 2011)
This study aimed to uncover the experience of being a fibrocystic. This is a descriptive exploratory study of qualitative phenomenological nature. The study population consisted of 9 fibrocystic patients: 2 children, 5 teenagers and 2 adults. The data collection was carried out through a semi-structured interview. The analysis of the transcribed speeches allowed us to reveal the phenomenon of being a fibrocystic patient, they experienced that when living with the chronic illness. It was possible to realize that cystic fibrosis was incorporated into their lives and that they have adapted to it. The fact that they have a serious illness and without cure has not changed their way of being and living, making them consider themselves normal people, like any other. The routine of treatments, hospitalizations and self-care are not interpreted as a bad thing, but necessary practices to control the disease for their own benefit.